2014
DOI: 10.3390/en7053282
|View full text |Cite
|
Sign up to set email alerts
|

A Boiler Room in a 600-Bed Hospital Complex: Study, Analysis, and Implementation of Energy Efficiency Improvements

Abstract: Abstract:The aim of energy efficiency is to use less energy to provide the same service. In hospitals, energy efficiency offers a powerful and cost-effective tool to reduce greenhouse gas emissions, fuel consumption, and also running costs. Over a six-month period, the six gas-fired boilers that provide both a hospital's heat and hot water were monitored. Analysis of the data obtained led to several actions being implemented in the hospital boiler room control system to improve the efficiency of the heat produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Fraile et al (2014) realized a study about energy efficiency improvements in a boiler room in a 600-bed hospital complex. They monitored six gas-fired boilers of heat and hot water over a six-month period and actions were implemented in the hospital boiler room control system to increase the efficiency of the heat production facilities [25].…”
Section: Improvement Of Air Conditioning and Heating Systems (Hvac)mentioning
confidence: 99%
“…Fraile et al (2014) realized a study about energy efficiency improvements in a boiler room in a 600-bed hospital complex. They monitored six gas-fired boilers of heat and hot water over a six-month period and actions were implemented in the hospital boiler room control system to increase the efficiency of the heat production facilities [25].…”
Section: Improvement Of Air Conditioning and Heating Systems (Hvac)mentioning
confidence: 99%
“…Therefore, the research on the index of hospital building energy consumption has been carried out all over the world. A study in German [1][2][3] found EPB was more suitable for evaluating hospital energy consumption. A Spain study got the same concluded with the German one, and furthermore it made 300 beds as the dividing line standardizing electricity, natural gas, diesel and other energy sources for the bed average energy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Healthcare engineering has become a relevant issue in hospital management, since one of its objectives is focused on energy and environmental efficiency of the building [7] and the fulfilment of the Environmental Biosafety conditions, keeping the perspective of patient safety [8].…”
Section: Introductionmentioning
confidence: 99%